(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Philippines is a tropical country and is home to thousands of species of flowering plants, including lemongrass, or tangled, in the local name, and typically used in cooking. According to research, lemongrass can repel mosquitoes, which are most likely to grow and dissipate in tropical countries. Because of the weather pattern in the Philippines, one of the common crises in the country is a vector-borne disease, an illness that results from an infection disseminated to humans by blood-feeding arthropods. To address the aforementioned issues, the usage of lemongrass as a natural repellent and scented gel could be a solution to reduce the use of synthetic mosquito repellent. The study’s findings determine the degree of acceptability of lemongrass as scented gel and mosquito repellant in terms of materials, procedural methodology, effectiveness, eco-friendly aspects, and presentation. Chemical engineers’ overall weighted mean score was 3.41, which is interpreted as “Highly Acceptable,” while environmental engineers’ score was 3.41, also interpreted as “Highly Acceptable”. There is no significant difference between the two sets of engineers since the acquired t-computed is 0.000 and is less than the acquired t-critical value of 0.706. The study’s findings determine the degree of acceptability in terms of cost, scent, effectivity, appearance, and user-friendliness. Low-income families overall weighted mean was 3.29, which is interpreted as “Highly Acceptable,” while the high-income families acquired an overall mean of 3.33, interpreted as “Highly Acceptable.” There is no significant difference between the two sets of families since the obtained t-computed is 0.139 and is less than the acquired t-critical value 2.306. For further enhancement of the product, the two different sets of groups of respondents recommended and suggested an enhanced and strong scent, a more balanced formulation, enhanced effectivity to a wide range, and improved repellency endurance. In terms of the product’s container, it is recommended to make it recyclable and reusable. It is also advised to make sure that a child cannot easily open the product’s container.